Anthrenus (s. str.) semipallens sp. nov., a new species from Spain (Coleoptera: Dermestidae: Anthreninae) - Holloway, Graham J.; Herrmann, Andreas (Zootaxa, 2023)
During an examination of Spanish Anthrenus spp. held in Andreas Herrmann’s private collection, four specimens of a new species were noted: Anthrenus (Anthrenus) semipallens. Images of habitus features, including antenna, are presented and compared with other Anthrenus species thought to occur in Spain. A. semipallens is small so some comparison species could be eliminated courtesy of size. Although A. semipallens doesn’t resemble the colour pattern of any other species, the possibility that A. semipallens is an unknown colour variant of a comparison species was considered. The A. semipallens specimens were dissected and the aedeagus compared with aedeagi from all other possible species. There was no similarity. Anthrenus semipallens is a valid new species.